1992
DOI: 10.1007/bf00194582
|View full text |Cite
|
Sign up to set email alerts
|

The role of sensory input in maintaining output from the locust oviposition digging central pattern generator

Abstract: A quantitative EMG analysis is presented of the effects of deafferentation on the motor program for oviposition digging in the locust Locusta migratoria. We examined the activity of two groups of antagonistic muscles, the opener and closer muscles of the ventral ovipositor valves, in terms of the cycle frequency, burst duration, and relative burst onset times. There were no significant differences between the pattern frequency produced in intact, semi-intact, or deafferented animals within 10 min of the onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…During this behavior mature females dig a hole in the ground in which the eggs are deposited. The digging process is a complex behavior, including substrate probing, digging, wall stabilizing (tamping), and egg deposition (Thompson, 1986;Rose et al, 2000), which requires sensory input for maintenance (Belanger and Orchard, 1992) and motor control. The response characteristics of tension receptors presented here showed their ability to monitor steady state tension as well as dynamic changes over a certain range (linear region of the steady state and dynamic response curve).…”
Section: Discussionmentioning
confidence: 99%
“…During this behavior mature females dig a hole in the ground in which the eggs are deposited. The digging process is a complex behavior, including substrate probing, digging, wall stabilizing (tamping), and egg deposition (Thompson, 1986;Rose et al, 2000), which requires sensory input for maintenance (Belanger and Orchard, 1992) and motor control. The response characteristics of tension receptors presented here showed their ability to monitor steady state tension as well as dynamic changes over a certain range (linear region of the steady state and dynamic response curve).…”
Section: Discussionmentioning
confidence: 99%
“…The neural substrate for the dorsal ovipositor valves has not been defined and therefore the specific location of these neurons is unknown at this time. The motor neurons are part of a CPG controlling digging behaviors that has been extensively analyzed and defined (27,28,33,34).…”
Section: Ovipositor Valves and Associated Skeletal Musclementioning
confidence: 99%
“…For example, the physical and chemical composition of the substrate is highly variable and locusts must adapt the oviposition rhythm to suit these needs (Popov, 1980;Woodrow, 1965). Belanger and Orchard suggested that the peptide proctolin was necessary for normal oviposition digging (Belanger and Orchard, 1993), where it is thought to play a role in muscle tension and in maintaining internal pressure (Rose et al, 2001). Clearly, in more compact substrates, the motor pattern would have to be modified in order to allow animals to excavate successfully, and such modulation by proctolin can aid in this.…”
Section: Regulation Of the Oviposition Rhythmmentioning
confidence: 99%